Sarcopenia as a Robust Predictor of Readmission within 6 Months among Individuals Experiencing Acute Stroke - Takafumi Abe; Yoshihiro Yoshimura; Yoichi Sato; Fumihiko Nagano; Ayaka Matsumoto (Annals of Geriatric Medicine and Research)
Background Sarcopenia negatively affects the short-term prognosis of hospitalized older adults. However, no evidence currently supports a direct relationship between sarcopenia and readmission among individuals who have experienced an acute stroke. Therefore, we investigated whether sarcopenia is associated with readmission after discharge. Methods This retrospective cohort study included patients who had experienced acute stroke. Sarcopenia was defined as the coexistence of low skeletal muscle mass index (SMI) and grip strength. We applied the log-rank test and Cox proportional hazards regression analysis to analyze whether sarcopenia, low SMI, and low grip strength were associated with readmission within 6 months. Results Among 228 included patients (mean age, 72.8 years; 146 males), the prevalence of sarcopenia was 24.6% (n=56; male 17.8%; female 36.6%). Cox proportional hazards regression analysis using the propensity score as a covariate revealed that sarcopenia (hazard ratio [HR]=7.21; 95% confidence interval [CI] 1.45–35.8; p=0.016) and low skeletal muscle mass (HR=7.40; 95% CI 1.14–48.1; p=0.036), but not low grip strength (HR=1.42; 95% CI 0.281–7.21; p=0.670), were significantly associated with readmission for stroke within 6 months. Conclusions Sarcopenia was negatively associated with readmission within 6 months of stroke onset in patients in Japan who had experienced an acute stroke. These findings suggest that the identification of sarcopenia may facilitate prognostic prediction from the acute stage and intervention(s) to prevent rehospitalization.